2018
DOI: 10.3390/ijms19082442
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulation by Ca2+-Activated K+ (BK) Channels Modulators in SH-SY5Y Neuroblastoma Cells

Abstract: The effects of Ca2+-activated K+ (BK) channel modulation by Paxilline (PAX) (10−7–10−4 M), Iberiotoxin (IbTX) (0.1–1 × 10−6 M) and Resveratrol (RESV) (1–2 × 10−4 M) on cell cycle and proliferation, AKT1pSer473 phosphorylation, cell diameter, and BK currents were investigated in SH-SY5Y cells using Operetta-high-content-Imaging-System, ELISA-assay, impedentiometric counting method and patch-clamp technique, respectively. IbTX (4 × 10−7 M), PAX (5 × 10−5 M) and RESV (10−4 M) caused a maximal decrease of the outw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…Also, it was not possible to use specific BK channel blockers, such as Ibtx or paxilline, because of their irreversible blocking action of the BK channel associated with antiproliferative effects [19,34]. Also, it should be noted that other potent and selective TRPV1 antagonist are available; in our experiments, we use capsazepine to block TRPV1 channel because of the its well-known pharmacology and the lack of action on cell proliferation and mineralization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was not possible to use specific BK channel blockers, such as Ibtx or paxilline, because of their irreversible blocking action of the BK channel associated with antiproliferative effects [19,34]. Also, it should be noted that other potent and selective TRPV1 antagonist are available; in our experiments, we use capsazepine to block TRPV1 channel because of the its well-known pharmacology and the lack of action on cell proliferation and mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, loss of function of the inwardly rectifying K + channel Kir2.1 impairs both osteoblastic and chondrogenic processes, leading to the rare Andersen’s syndrome [18]. Furthermore, we previously demonstrated that large-conductance Ca 2+ -activated K + (BK) channels are involved in cell proliferation, since the incubation of SH-SY5Y cells with BK channel antagonists paxilline, iberiotoxin, and resveratrol was associated with a reduction of cell proliferation, reducing cell diameter and inducing AKT1p ser473 dephosphorylation [19].…”
Section: Introductionmentioning
confidence: 99%
“…27,28 This finding was also consistent with that by Zhou et al who also observed BK channels expression in HCC cells. 29 Before our research on BK channels in HCC, previous studies reported that BK channels in various cancer cells such as triple-negative breast cancer cells, 18 neuroblastoma cells, 19 human glioblastoma cells 21,22 and human astrocytoma cells. 30 We examined BK channel expression in HCC patients and assessed the association of its expression with overall survival, with data obtained from online TCGA library.…”
Section: Discussionmentioning
confidence: 99%
“…The BK Ca channel antagonists paxilline (1), progesterone (2) and genistein (3) fit across the length of the cGMP structure (Figure 4). Paxilline, in common with thapsigargin and cyclopiazonic acid, enhances apoptosis mediated by TRAIL (tumour necrosis factor-related apoptosis-induced ligand) and regulates the cell cycle of neuroblastoma cells (Kang et al 2011;Maqoud et al 2018). Progesterone and genistein induce apoptosis and protect against apoptosis (Table 1); both compounds have the same O6-O8 atomic distance, nucleotide fit and BK Ca channel blocking activity.…”
Section: Modulators Of Apoptosismentioning
confidence: 99%